If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 144 = -12(x + 5) + -1 Reorder the terms: 144 = -12(5 + x) + -1 144 = (5 * -12 + x * -12) + -1 144 = (-60 + -12x) + -1 Reorder the terms: 144 = -60 + -1 + -12x Combine like terms: -60 + -1 = -61 144 = -61 + -12x Solving 144 = -61 + -12x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '12x' to each side of the equation. 144 + 12x = -61 + -12x + 12x Combine like terms: -12x + 12x = 0 144 + 12x = -61 + 0 144 + 12x = -61 Add '-144' to each side of the equation. 144 + -144 + 12x = -61 + -144 Combine like terms: 144 + -144 = 0 0 + 12x = -61 + -144 12x = -61 + -144 Combine like terms: -61 + -144 = -205 12x = -205 Divide each side by '12'. x = -17.08333333 Simplifying x = -17.08333333
| 0.45x+0.05(18-x)=0.10(-31) | | 56=2-6m | | 4u-7=u+(4+u) | | -243=-9(10+x)-2 | | 69x-18-9x=11+60x-29 | | 27-3x=9 | | .25x-.05(4-x)=.10(-2) | | 7(6-(2*-37))=5((-3*-37)+1) | | 9+2r-1=9r+17-6r | | 5x+2=-1a | | x+13i=y-yi | | -4y+2-5=2y | | 2x-4(x-4)=-2+5x-3 | | 3(1-3x)-1=(-3x-2)-4x | | 3(3x-4)-16=6x-1 | | 3x+40+2x=90 | | 15z^2+14z+3= | | -1/5(-25x+15)=20 | | 15=(1-3x)+x | | x^2-0x-49=0 | | 5(y+-3)=19 | | 3x-50+2x-5=90 | | 1.10x+1200=2.50 | | 9(2N+3)=6(7n+4)+5 | | 6-(n-3)=2 | | (4h+1)+12h=36 | | (4h+1)12h=36 | | 1/6(36x+12)=10 | | 17=4(x-2)+2x | | [3y-2]+4=10 | | 3-(n+10)=4 | | 5x+7*20= |